Title IX: the Female Intercollegiate Athletic Sphere - Basma, Nayla (Columbia Undergraduate Research Journal, 2018)
Title IX consists of just thirty-seven words, and it is these words that have transformed the dynamics of the female athletic sphere in the United States. Although the federal law was initially envisioned to assist women in academia, it is currently renowned for its profound impact on American sports [12]. It is an irrefutable fact that Title IX has vastly increased women’s participation in sports, reportedly increasing female participation rates within colleges six-fold from 1972—the year it was passed—to today [3]. Yet, despite the progress made by Title IX, it faces deep challenges in its quest to achieve true equality. Women’s participation rates in sports still lag far behind men, and one cannot ignore this troubling reality that persists in the United States[5]. Thus, the question as to whether or not Title IX has achieved gender equity is highly debatable. This paper intends to illuminate the shortcomings of Title IX’s goal in attaining true equality through analysis of its limitations. Specifically, the essay will first discuss the historical attitudes towards women in sports before Title IX and the structure of the federal law. It will then explore the issues inherent in Title IX, such as the continuation of male preservation, the reduction of men’s sports, and sexual harassment. The scope of this essay will focus mainly on intercollegiate sports.